TECTONIC AND SEISMIC CONDITIONS FOR CHANGES IN SPRING DISCHARGE ALONG THE GARNI RIGHT LATERAL STRIKE SLIP FAULT (ARMENIAN UPLAND) - Léonardi V.; Arthaud F.; Tovmassian A.; Karakhanian A. (My University, 1998)
This study presents the relationship between local seismicity and springs discharge, in which the microseismicity modifies the state of stress of the aquifer matrix and these modifications of the local stress control the aquifer behaviour from an example of a basaltic reservoir crossed by a seismic fault. Along the right-lateral Garni seismic wrench fault, the distribution in space and time of more than 500 micro-earthquakes has been studied providing a pattern of stress distribution. Together with this tectonic survey, the hydrographs of springs issuing from an aquifer located in basaltic lava flows and crossed by the fault have been gauged for 4 years. According to its tectonic, geologic and hydrodynamic properties, the reservoir has been divided in to several parts. The hydrological behaviour of the reservoir and of each of its parts has been modelled, based on the rainfall and hydrodynamic properties of the basaltic reservoir and of nearby reservoirs. The model allows us to define the ‘normal behaviour’ of the springs, when their discharge is not affected by an earthquake. Anomalies to the normal hydrometric curves are defined, and correlated to small (M < 3.5) earthquakes along the Garni fault. We propose that the circulation of underground water in the area around the fault depends largely on the fracture pattern of the basalts and the aquifer basement, as pointed out from field observations. Changes in spring discharges are explained by variations in the state of stress around the Garni fault, induced by the alternation of elastic strain and stick-slip movement on the fault, and by creep far from the fault. A model of stress distribution is proposed which explains changes in fracture charateristics before and after earthquakes.